1965
DOI: 10.1002/app.1965.070090919
|View full text |Cite
|
Sign up to set email alerts
|

Crystallinity of ethylene–vinyl acetate copolymers

Abstract: SynopsisDetermination of crystallinity of ethylene-vinyl acetate copolymers according to the usual x-ray diffraction method employed for polyethylene is very much hampered by the fact that these copolymers are usually largely amorphous and the Bragg reflections in their daraction diagrams which are therefore broad and weak are drowned by the strong and dominant amorphous halo. As a consequence it is virtually impossible to carry out a realistic resolution of the total diffraction diagram into the individual Br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

1967
1967
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(13 citation statements)
references
References 1 publication
0
13
0
Order By: Relevance
“…The EVA of lower VA content is similar to polyethylene, which has adequate ability to crystallize. As the VA content increases, the pendent acetoxy group prevents adjacent polyethylene chains to form crystal lattice, which results in lower levels of crystallinity …”
Section: Resultsmentioning
confidence: 99%
“…The EVA of lower VA content is similar to polyethylene, which has adequate ability to crystallize. As the VA content increases, the pendent acetoxy group prevents adjacent polyethylene chains to form crystal lattice, which results in lower levels of crystallinity …”
Section: Resultsmentioning
confidence: 99%
“…This effect could account for the consistency in T g s observed for bulk PEVAc copolymers with small vinyl acetate contents. 33,35,36 The PEVAc copolymer is expected to be totally amorphous when it contains over 45% vinyl acetate, 33,43 which explains the significant increase in T g for PEVAc (70% VAc) compared with the other PEVAc copolymers. The differential conformational mobility of the amorphous polymer chains with different proximity to the ethylene crystallites resulted in broad glass transitions for the copolymers containing small amount of vinyl acetate.…”
Section: Discussionmentioning
confidence: 99%
“…Its properties are easily variable by the adjustment of the comonomer ratio. When the VAc content is low, the copolymer is more akin to polyethylene and has enough ability to crystal, but for high VAc content the pendent acetoxy is excessive enough and prevents adjacent polyethylene chains packing into the crystal lattice [2], then totally amorphous and rubber-like EVA is expected when the VAc content is more than 43% by weight as indicated by Kamath and Wakefield [3]. It should be noticed that Varga and his coworkers revealed that the crystallization and melting characteristics of PE are very sensitive to the VAc content [4].…”
Section: Introductionmentioning
confidence: 98%